Model kinetika inhibisi substrat pada pertumbuhan Kluyveromyces lactis - Akbarningrum Fatmawati (Jurnal Teknik Kimia Indonesia, 2009)
Substrat inhibition kinetic model of Kluyveromyces lactis growthFood industry waste such as whey may be utilized as substrates in fermentation processes. Kluyveromyces lactis is yeast that can metabolize the lactose content of whey. In fermentation process design, the kinetics data and growth model of the microorganism are essential. This research was done to identify the growth kinetic model of Kluyveromyces lactis FNCC 3024 in lactose, glucose, and galactose substrates. Substrate concentration was varied as 5, 10, 20, 50, 100, and 150 g/L. Yeast growth profile in glucose and lactose substrates indicated substrate inhibition effect, while the growth profile in galactose substrate did not. Non-competitive substrate inhibition kinetic model was more suitable for glucose and lactose models, with a relatively small sum of squares of errors, namely 9.956 x 10-3 for glucose and 3.777 x 10-3 for lactose. Monod kinetic model for galactose substrate produced the lowest sum of squares of errors, namely 1.358 x 10-3. The maximum specific growth rate obtained from the modeling for glucose, lactose, and galactose substrates were 0.295, 0.265, and 0.147 hour-1.Keywords: kinetics, growth, inhibition, substrate, Kluyveromyces lactis Abstrak Limbah industri makanan seperti whey dapat dimanfaatkan sebagai substrat dalam proses fermentasi. Kluyveromyces lactis adalah salah satu ragi yang dapat memetabolisme kandungan laktosa dari whey. Pada perancangan proses fermentasi sangat diperlukan data kinetika dan model pertumbuhan dari mikroorganisme. Penelitian ini dilakukan untuk mengetahui model kinetika pertumbuhan batch Kluyveromyces lactis FNCC 3024 pada substrat laktosa, glukosa dan galaktosa. Konsentrasi substrat divariasi sebesar 5, 10, 20, 50, 100 dan 150 g/L. Profil pertumbuhan ragi pada substrat glukosa dan laktosa menunjukkan adanya inhibisi substrat sedangkan profil pertumbuhan pada substrat galaktosa inhibisi substrat tidak tampak. Model kinetika inhibisi subtrat non-kompetitif lebih tepat digunakan untuk substrat glukosa dan laktosa dengan kuadrat beda yang cukup kecil yaitu 9,956 x 10-3 untuk glukosa dan 3,777 x 10-3 untuk laktosa. Model kinetika Monod untuk substrat galaktosa memberikan jumlah kuadrat residual terkecil yaitu 1,358 x 10-3. Laju pertumbuhan spesifik maksimum yang dihasilkan dan pemodelan untuk substrat glukosa, laktosa dan galaktosa berturut-turut adalah 0,295, 0,265 dan 0,147 jam-1.Kata kunci : kinetika, pertumbuhan, inhibisi, substrat, Kuyveromyces lactis